2012
DOI: 10.1111/j.1399-3089.2011.00686.x
|View full text |Cite
|
Sign up to set email alerts
|

Porcine alanine transaminase after liver allo‐and xenotransplantation

Abstract: Aspartate transaminase (AST) and alanine transaminase (ALT) are measured following liver transplantation as indicators of hepatocellular injury. During a series of orthotopic liver allo-and xenotransplants, we observed that there was an increase in AST in all cases. The anticipated concomitant rise in ALT did not occur when a wild-type (WT) pig was the source of the liver graft, but did occur when a baboon or a genetically engineered (α1,3-galactosyltransferase gene-knockout [GTKO]) pig was the source of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 18 publications
(15 reference statements)
5
13
1
1
Order By: Relevance
“…The increase in the ALT and AST levels after the first 12 hours suggested that serious liver damage had occurred at the early post‐Tx stage. The total rise in bilirubin was continuous until euthanasia, which is consistent with the findings of previous reports . The coagulation parameters were normal or near‐normal in our models.…”
Section: Discussionsupporting
confidence: 92%
“…The increase in the ALT and AST levels after the first 12 hours suggested that serious liver damage had occurred at the early post‐Tx stage. The total rise in bilirubin was continuous until euthanasia, which is consistent with the findings of previous reports . The coagulation parameters were normal or near‐normal in our models.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings of a disproportionate rise in the AST relative to the ALT in xenoperfusion experiments confirm results noted in other experiments [28]. The mechanisms underlying this phenomenon have yet to be elucidated.…”
Section: Time (Min)supporting
confidence: 91%
“…In our recent experience in liver xenotransplantation (18), we observed that pig alanine transaminase (ALT), but not aspartate transaminase (AST), in GTKO pigs is significantly lower than in WT pigs, but similar to human and baboon levels (19). We hypothesized that there would be other differences in hematologic, biochemical, and coagulation parameters between WT and GTKO pigs.…”
Section: Introductionmentioning
confidence: 99%